Prinsip Keharusan Label Sertifikasi Halal pada Barang Gunaan dalam Perniagaan Islam - Wahyudin Darmalaksana; Widodo Dwi Ismail Aziz (UIN Sunan Gunung Djati Bandung, 2022)
This study aims to discuss the principle of mandatory halal certification labeling on used goods. This study uses a qualitative approach by applying the descriptive-analytical method. The results of this study indicate that the halal certification label for used goods is useful as consumer protection and at the same time an advantage for producers in maintaining consumer loyalty. The necessity of a halal certification label can be understood through the basic principles in Islamic commerce, namely shidiq, amanah, tabligh and fathonah. This study concludes that the mandatory halal certification label already has a foundation of universal Islamic commerce principles so that it plays a role in providing guarantees to consumers in the provision of healthy, clean, good, and safe goods.